Hypoglossal nerve paresis secondary to anterior approach of upper cervical spine followed by spontaneous recovery - López, Antonio José Vargas; Quarante, Laín Hermes González; de Sagredo del Corral, Oscar Lucas Gil; Afonso, Antonio Montalvo; Carballal, Carlos Fernández (Journal of Spine Surgery, 2017)
We describe an exceptional complication of cervical spine surgery in a 63-year-old male. He suffered the impact of a beam to the top of his head. During evaluation in the emergency room he reported intense neck pain with no other neurological symptoms or findings on physical examination. Spine computed tomography (CT) showed C3 vertebral body fracture that required surgical stabilization. A right side anterior approach to upper cervical spine with C3 corpectomy and placement of iliac bone autograft was performed. After surgery the patient presented dysphagia, dysarthria and limitation tongue mobility to the right side. These findings were consistent with hypoglossal neuropraxia probably related to soft tissue traction generated by the upper part of the self-retaining retractor. After discharge the patient experienced spontaneous improvement of hypoglossal paresis.